IMPLEMENTASI PEMBELAJARAN PROJECT BASED LEARNING (PBL) DALAM UPAYA MENINGKATKAN PEMAHAMAN DAN PENGETAHUAN AKUNTANSI - Anggadini, Sri Dewi; Damayanti, Sari; Suryanagara, Gagan; Sukmawati, Ira; Fahrana, Egi; Fitriyanti, Dini (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
The research objective was to determine the magnitude of the influence of Project Based Learning (PBL) learning in accounting practicum courses in an effort to increase accounting understanding and knowledge. Learning in tertiary institutions is an interaction between lecturers and students which is supported by various elements such as objectives, subject matter, infrastructure, learning environment, learning methods, and evaluation. All of these elements greatly affect the success of the teaching and learning process. One of the important subjects is the Accounting Practicum, where the use of the right learning model will greatly affect the success of the learning process. Conventional methods that only focus on material from lecturers to students are now considered less effective. More active learning methods are needed, one of which is the Project Based Learning method. The higher education curriculum in Indonesia should be directed at Case Project Based Learning, where students learn through case analysis and problem-solving. This will acquire skills as a reliable project-solver and better prepare them to enter the world of work. The population in this study were active students in the Accounting study program. The data analysis technique used is a descriptive analysis of the Likert scale. Approaches that help in learning accounting practices Most respondents agreed that PBL helps them in learning accounting practices, and no respondents considered this program less useful.